Analysis of capital sources, owner objectives, and determinants of performance of wine farms in the Western Cape - Nakana, Elvis (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScAgric (Agricultural Economics))--University of Stellenbosch, 2009.